Separate roles for the DNA damage checkpoint protein kinases in stabilizing DNA replication forks - Mónica Segurado; John F.X. Diffley (2008)
The DNA damage checkpoint plays a crucial role in maintaining functional DNA replication forks when cells are exposed to genotoxic agents. In budding yeast, the protein kinases Mec1 (ATR) and Rad53 (Chk2) are especially important in this process. How these kinases act to stabilize DNA replication forks is currently unknown but is likely to have important implications for understanding how genomic instability is generated during oncogenesis and how chemotherapies that interfere with DNA replication could be improved. Here we show that the sensitivity of rad53 mutants to DNA-damaging agents can be almost completely suppressed by deletion of the EXO1 gene, which encodes an enigmatic flap endonuclease. Deletion of EXO1 also suppresses DNA replication fork instability in rad53 mutants. Surprisingly, deletion of EXO1 is completely ineffective in suppressing both the sensitivity and replication fork breakdown in mec1 mutants, indicating that Mec1 has a genetically separable role in replication fork stabilization from Rad53. Finally, our analysis indicates that a second downstream effector kinase, Chk1, can stabilize replication forks in the absence of Rad53. These results reveal previously unappreciated complexity in the downstream targets of the checkpoint kinases and provide a framework for elucidating the mechanisms of DNA replication fork stabilization by these kinases.